Effect of Irradiation and Curry Leaves Extract on Quality Attributes and Shelf Life of Chicken Emulsion - Muthukumar, M.; Ravi, T.; Kumar, M. Shashi; Reddy, K. Sudhakar; Krishnaiah, N. (Journal of Meat Science, 2014)
The present study was conducted to evaluate the effect of irradiation and antioxidants on quality attributes and shelf life of the chicken emulsion during refrigerated storage. Four treatments evaluated include: Control (without irradiation and antioxidant), T1 (irradiation without antioxidant), T2 (butylated hydroxyl anisole–(BHA) - 0.02%) and T3 (450 ppm equivalent curry leaves (Murrayakoenigii) phenolics. Total phenolic contents (mg per gram of powder) as tannic acid equivalent of curry leaves was ranged from 6.78 to 7.27. There was a concentration dependent increase in reducing power (absorbance value of 0.3 at 50 μg phenols to 0.9 at 50 μg phenols) and 1,1-diphenyl 2-picrylhydrazyl (DPPH) radical scavenging activity (70% at 50 μg phenols to 85% at 250 μg phenols) of curry leaves extract. Highly significant differences (P
Keywords: BHA; Chicken emulsion; Curry leaves; Irradiation; Lipid oxidation; Natural antioxidants